Development of the reproductive phase of Lepidium meyenii ''maca'' in Costa conditions, Trujillo, Peru - López Medina, Segundo Eloy (2021)
Lepidium meyenii “maca”, is an Andean crop highly valued for its nutraceutical properties, as it has antioxidant action, in addition to improving fertility, memory, energy, as well as regulating glucose levels and blood pressure. Its cultivation is restricted to the highlands of Peru, having a biennial or annual behavior, depending on the altitude, the reproductive phase needing a period of around 5 months to culminate with seed production; Furthermore, its reproductive phenology in Costa is still unknown. Therefore, it was proposed as a research objective to determine the development of the Lepidium meyenii “maca” reproductive phase under coastal conditions. For this, hypocotyls were collected from the La Hermelinda Market, which were selected, disinfected and cultivated in a demonstration plot in the University City of the National University of Trujillo, where the data referring to the days of duration of the reproductive phase were recorded, covering: Emergence, flower bud formation, full flowering and fruiting. It is concluded that the reproductive phase of L. meyenii “maca” lasts 68 days in coastal conditions, facilitating the obtaining of botanical seed in a shorter time, which will contribute to the installation of seedlings at the coast level.